Getting more efficient Rapid Response System (RRS) utilization by the use of a general ward based deteriorating patient contract. Issue 1 (December 2015) - Buist, Michael; Marshall, Stuart; Shearer, Bill; Finnigan, Monica; Hore, Tonina; Sturgess, Tamica; Wilson, Stuart
Abstract Objective To determine if a general ward-based plan to address the deteriorating patient could improve RRS utilization over and above a mandatory organizational policy and procedure. Design A two stage methodology: First, engagement with ward providers and users of the RRS to generate ward-based interventions; Second, measurement of the incidence of missed/delayed RRS calls, RRS calls, cardiac arrests and unplanned intensive care unit admission both prior to the intervention and 12 months post implementation. Setting Monash Health is a comprehensive healthcare network with 570 adult in-patient beds across four metropolitan teaching hospitals in the south-eastern sector of Melbourne. Results The interventions selected for intervention were: (1) a ward based agreement on how to best locally optimize management of the deteriorating patient, (2) an improved communication protocol, and (3) a revision of the education program for staff. Post intervention the aggregate rate of missed/delayed RRS calls reduced across all wards (1.05 to 0.34 per 1000 bed days, p = 0.049). This occurred without a change in the rate of RRS activation (7.98 per 1000 bed days pre-intervention versus 7.85 bed days post-intervention). The incidence of cardiac arrests or unplanned interventions did not change post intervention. Conclusions Engagement of the users of a system like the RRS activation protocol can improve compliance rates with protocols when the users have ownership of the process.